Anthropogenic flash floods and climate change in rural Zimbabwe: Impacts and options for adaptation - Mugambiwa, Shingirai; Makhubele, Jabulani (Technium Social Sciences Journal, 2021)
Zimbabwe has been affected by numerous floods-related disasters in the recent past. These disasters often left rural communities in difficult socioeconomic situations. Floods are among the major water-related hazards and natural disasters worldwide. They are associated with excess rainfall, resulting in river overflow due to climate change . Developing countries constitute a large number of losses caused by water hazards. Thereby, in these countries, the vulnerabilities of households that depend on rain fed agriculture and livestock production for their livelihoods increases. This review paper seeks to establish the association between anthropogenic flash floods and climate change and unearth the impacts; vulnerabilities and adaptation options associated with anthropogenic flash floods in rural Zimbabwe. The study found that numerous anthropogenic activities perpetuate an increase in flood risk. These include littering, river or dam regulation measures, intensified land use and emissions of greenhouse gases, which subsequently result in global climate change. The impacts of flash floods established in the study include drought, food insecurity, displacements, malnutrition and severe effects on subsistence economy. The study concluded that even though most rural communities in Zimbabwe are vulnerable to the effects of floods, they have devised numerous diverse adaptation strategies to cope with the changes in the environment.